The Social Psychology of Perceiving Others Accurately 2016
DOI: 10.1017/cbo9781316181959.006
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of perceiving social attributes

Abstract: A wealth of research shows that people can achieve accurate interpersonal judgments of others based on brief observations of their nonverbal cues. Here, we review evidence demonstrating that people can accurately judge others' kinship, sexual orientation, religious identity, political ideology, and professional success from subtle cues in their physical appearance and expressive behavior. Following this discussion, we detail some of the major factors that can influence the accuracy of these judgments. Finally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(14 citation statements)
references
References 89 publications
1
11
0
Order By: Relevance
“…The broad domain of social attributes contains relatively stable characteristics, including religious identity, political ideology, sexual orientation, socioeconomic status, values, attitudes, and kinship. While perceptions in this domain may often contain biases, research has shown that individuals have nearly perfect accuracy when identifying a target's age, race, and sex (e.g., Macrae & Martin, 2006) and can accurately categorize ambiguous social groups at better than chance rates (Alaei & Rule, 2016). In one of the first studies examining interpersonal accuracy of social attributes, Ambady and colleagues (1999) found that individuals could accurately perceive targets' sexual orientation from short videos and still photographs.…”
Section: Social Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…The broad domain of social attributes contains relatively stable characteristics, including religious identity, political ideology, sexual orientation, socioeconomic status, values, attitudes, and kinship. While perceptions in this domain may often contain biases, research has shown that individuals have nearly perfect accuracy when identifying a target's age, race, and sex (e.g., Macrae & Martin, 2006) and can accurately categorize ambiguous social groups at better than chance rates (Alaei & Rule, 2016). In one of the first studies examining interpersonal accuracy of social attributes, Ambady and colleagues (1999) found that individuals could accurately perceive targets' sexual orientation from short videos and still photographs.…”
Section: Social Attributesmentioning
confidence: 99%
“…In one of the first studies examining interpersonal accuracy of social attributes, Ambady and colleagues (1999) found that individuals could accurately perceive targets' sexual orientation from short videos and still photographs. Overall, research suggests that the cognitive processes used to make perceptions about obvious discrete social groups are the same processes used to make perceptions about more ambiguous social groups (Alaei & Rule, 2016).…”
Section: Social Attributesmentioning
confidence: 99%
“…Numerous studies have investigated the accuracy of perceptions of others’ social attributes and personality characteristics. For example, people can categorize others according to sexual orientation, political affiliation, and some personality traits on the basis of photos or brief videos with better than chance accuracy (Alaei & Rule, 2016; Tackett, Herzhoff, Kushner, & Rule, 2016; Tskhay & Rule, 2013). A related focus of study, which psychologists have approached in diverse ways, concerns whether trustworthiness impressions predict behavior.…”
Section: Accuracy In Person Perceptionmentioning
confidence: 99%
“…They tell us little about the person or their intentions, unless they are interpreted as an emotional reaction, such as a sign of anxiousness. In contrast, emotion expressions signal a variety of socially relevant information (Alaei & Rule, 2016) and behavioral intentions (Hess, Blairy, & Kleck, 2000). Specifically, some expressions such as happiness and sadness signal affiliative intentions, whereas others, such as anger and disgust, signal the opposite (Knutson, 1996).…”
Section: Introductionmentioning
confidence: 99%